The Effect of Return on Assets, Interest Rates, and Inflation on Stock Prices in Private Banks 2015-2023 - Renita Melinda; Kartika Berliani (eCo-Buss, 2024)
The objective of this research is to examine the impact of inflation, interest rates, and return on assets (ROA) on the stock prices of private banks that are listed on the Indonesia Stock Exchange between 2015 and 2023. With approaches to verification and description, the research methodology is quantitative. The financial reports from banking sub-sector companies obtained through documentation approach and literature review constitute the secondary data used. The study sample, which included Bank OCBC NISP (NISP), Bank BCA (BBCA), and Bank Permata (BNLI), was selected using purposive sampling. Descriptive and verification statistics, such as multiple linear regression and traditional assumption tests, were used to analyse the data. The t-test results indicate that while interest rates have a nearly substantial negative link with stock prices, inflation has no significant effect on stock prices, and return on assets (ROA) has a large positive effect. The findings of the F test demonstrate that the combination of ROA, interest rates, and inflation in the regression model significantly affects stock prices. According to the study, the stock prices of Indonesian private banks show no obvious effect from inflation, financial performance (ROA) and interest rates are major drivers. For investors and financial managers making financial strategy and investment decisions, these findings offer insightful information.